2019
DOI: 10.1039/c9cc05988a
|View full text |Cite
|
Sign up to set email alerts
|

Spin-crossover iron(ii) complex showing thermal hysteresis around room temperature with symmetry breaking and an unusually highT(LIESST) of 120 K

Abstract: The Fe(ii) complex of 4′,4′′ carboxylic acid disubstituted dipyrazolylpyridine shows spin-crossover around room temperature and the LIESST effect with T(LIESST) of 120 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…This suggests that a complete and abrupt spin conversion from the HS to LS state is achieved at a T 1/2 cooling of 278 K. Heating the sample leads to another abrupt spin conversion at 286 K ( T 1/2 warming ), giving a narrow thermal hysteresis loop of 8 K, centered ( T c ) at 282 K (9 °C). It should be pointed out that 3 belongs to one of the very particular SCO complexes that show a very abrupt spin transition with the hysteresis loop near the RT region, 15,16,18–22,64–66 which makes it an excellent candidate for molecular switches and memory devices in practical applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that a complete and abrupt spin conversion from the HS to LS state is achieved at a T 1/2 cooling of 278 K. Heating the sample leads to another abrupt spin conversion at 286 K ( T 1/2 warming ), giving a narrow thermal hysteresis loop of 8 K, centered ( T c ) at 282 K (9 °C). It should be pointed out that 3 belongs to one of the very particular SCO complexes that show a very abrupt spin transition with the hysteresis loop near the RT region, 15,16,18–22,64–66 which makes it an excellent candidate for molecular switches and memory devices in practical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decades, great efforts dedicated to achieving SCO materials with an abrupt and hysteretic thermal loop centered near room temperature have been made, 15–23 as the near room temperature transition is a prerequisite for a realistic application. Interestingly, it has been demonstrated that the profiles of a spin transition curve and critical temperature are associated with the cooperative effect of individual SCO centers.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal complexes that exhibit spin crossover (SCO), arguably, offer one of the most appealing examples of molecular bistability, which manifests itself as dramatic changes in structural, optical, magnetic, and dielectric properties of the SCO material. 1,2 The large disparity in properties between the high-spin (HS) and low-spin (LS) electronic congurations 3 offers a convenient parameter space to manipulate the bistable behavior by variations in temperature, [4][5][6][7] pressure, [8][9][10][11][12][13] or light irradiation. [14][15][16][17][18][19][20] In recent years, SCO building blocks have been actively explored in the pursuit of multifunctional molecule-based materials that would combine spin-state switching with other useful functional properties, such as conductivity, magnetic ordering, or luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts have been devoted to constructing bistable metal organic frameworks (MOFs) that show excellent performance in power dissipation, response time, and selectivity, meanwhile possess switchable photoinduced phase transition at room temperature [4][5][6][7][8]. The light-induces excited spin state trapping (LIESST) effect has made the single-molecule level photoswitch possible [9,10]. A large number of iron(II) SCO complexes [11,12] and a small amount of mononuclear cobalt(II) SCO complexes [13] with corresponding ligand derived from bi-/terpyridine [14], amido-aryl ligands [15], 4-terpyridone [16], or 3-formylsalicylic acid [17] have been observed.…”
Section: Introductionmentioning
confidence: 99%